1993
DOI: 10.1128/jb.175.2.510-518.1993
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of host ranges of Bacillus sphaericus mosquito larvicidal toxins

Abstract: The 51.4-kDa-41.9-kDa binary toxin produced by different strains of Bacillus sphaericus shows differential activity toward Culex quinquefasciatus, Aedes atropalpus, and Aedes aegypti mosquito larvae. The patterns of larvicidal activity toward all three mosquito species and growth retardation in A. aegypti have been shown to be due to the 41.9-kDa protein. By using mutant toxins expressed in Escherichia coli, insecticidal activity and growth retardation correlated with amino acids centered around position 100 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 21 publications
0
42
0
2
Order By: Relevance
“…Because the highest proportion of Cyt1A-to-spore-crystal was associated with the lowest synergism level, the higher proportion of Cyt1A in tests using crystal may also have contributed to the decreased synergism. However, the role of spores in the observed synergism cannot be ruled out because B. sphaericus 2362 spores have been shown to be toxic to Aedes (4).…”
Section: Discussionmentioning
confidence: 99%
“…Because the highest proportion of Cyt1A-to-spore-crystal was associated with the lowest synergism level, the higher proportion of Cyt1A in tests using crystal may also have contributed to the decreased synergism. However, the role of spores in the observed synergism cannot be ruled out because B. sphaericus 2362 spores have been shown to be toxic to Aedes (4).…”
Section: Discussionmentioning
confidence: 99%
“…There are various approaches to broadening the insecticidal spectrum of B. thuringiensis, including introduction of toxin genes that code for separate insecticidal activities into a recipient bacterium (4,7,26), creating a bacterium that expresses a combination of toxins instead of a single toxin (46), and engineering mutant toxins with new or broadened insecticidal spectra (6,8). In these approaches, multiple gene constructs with separate mechanisms of action are useful to forestall resistance development.…”
mentioning
confidence: 99%
“…Significance of this interaction is emphasized in the work showing that amino acid at position 93 of BinA is important for biological activity of the toxin by playing a major role in the formation of BinA-BinB complex (15). Also, amino acids centered around position 100 in BinA which has been proved to be important for host ranges of binary toxin may play a part in BinA-BinB interaction (14). In order to explore the possible role of C67 and C161 of BinB in function of binary toxin, binding between BinA and BinB mutants were tested employing dot blot analysis.…”
Section: Effect Of Amino Acid Substitutions On Bina-binb Interactionmentioning
confidence: 99%
“…In the same report, it was suggested that both Nand C-terminal regions of BinA are important for BinA-BinB interaction (8). Site-directed mutagenesis of amino acid positions 93, 99, and 104 of BinA revealed that these residues are crucial for toxicity and it was proposed that residues in this region might play a role in the formation of BinA-BinB complex (14,15). Interestingly, mutagenesis of charged residues (R97, E98, R101, and E114) in the same region showed that these charged residues are also essential for biological activity of binary toxin, but not involved in BinA-BinB interaction (16).…”
Section: Introductionmentioning
confidence: 98%